The Exiting Legal Provisions and Challenges in Intellectual Property and Data Protection Laws in India With Respect To Artificial Intelligence (International Journal of Innovative Research in Engineering & Management, 2022)
The technology of today’s world are  continuously change with computer, robots and machine,  replacing simple human activities. Artificial intelligence is  one of them innovation. Many sectors are getting benefited  from this new technology but other side of this technology  misused in various sector as like personal and profession. The Intellectual Property Rights (IPR) and also AI stem  from the world intelligence. The copyright law of India  declare states that an effort is to remain qualify aimed at copyright defence their uses to be a modicum of creativity  standard. This paper disclose about AI working module,  Intellect stuff right of India, copyright act in India, Indian  patent Act, The design Act and privacy. Artificial  Intelligence determination be playing a significant part in  the development of patent law itself. AI based on  Computer system, which is designed and also drafting the  current industrial design protection laws and legislations  may not declare to be enough provide them desired  protection.
Keywords: Artificial Intelligence; Copyright Protection; Intellectual Property; Indian Patent; Patent Law